2012
DOI: 10.1038/cgt.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a glioma-specific immune response by oncolytic parvovirus Minute Virus of Mice infection

Abstract: Rodent autonomous parvoviruses (PVs) are endowed with oncotropic properties and represent virotherapeutics with inherent oncolytic features. This work aimed to evaluate the capacity of Minute Virus of Mice (MVMp) to act as an adjuvant stimulating a mouse glioblastoma-specific immune response. MVMp was shown to induce cell death through apoptosis in glioma GL261 cells. Antigen-presenting cells (APCs) provide the initial cue for innate and adaptive immune responses, and thus MVMp-infected GL261 cells were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Long-term survival in response to oncolytic virotherapy has been shown to be associated with priming of a tumor-reactive adaptive immune response (24)(25)(26). To test whether this was also occurring in the present model, we rechallenged mice surviving the initial CT-2A-Fluc implantation with a second intracranial implantation of 5 ϫ 10 4 CT-2A-Fluc cells.…”
Section: Resultsmentioning
confidence: 90%
“…Long-term survival in response to oncolytic virotherapy has been shown to be associated with priming of a tumor-reactive adaptive immune response (24)(25)(26). To test whether this was also occurring in the present model, we rechallenged mice surviving the initial CT-2A-Fluc implantation with a second intracranial implantation of 5 ϫ 10 4 CT-2A-Fluc cells.…”
Section: Resultsmentioning
confidence: 90%
“…These data support the view that in vitro studies of this sort are inferential and that, ultimately, in vivo experiments are needed. There are several factors that might underlie the reduced efficacy of VSV-EBOV-GP compared with VSV-LASV-GPC in vivo, including in vivo transformation of tumors to forms that are more resistant to infection by some viruses (55) and the existence of a greater number of cells and mechanisms for defeating virus infections even in immunocompromised mice that might be differentially activated or attenuated by viral glycoproteins. Furthermore, we cannot rule out the possibility that some types of tumors may show a greater in vivo susceptibility to VSV-EBOV-GP than found with gliomas here.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficiency in replication and oncolytic activity is improved using LuIII, a specific capsid protein. Grekova et al showed the induction of an immune response and protection from future glioma challenge after treatment with parvovirus [95]. Parvovirus is currently being studied in a Phase I/IIa clinical trial in recurrent GBM [53].…”
Section: Oncolytic Virusesmentioning
confidence: 99%